Pengembangan Sistem Pengelolaan Praktek Kerja Lapangan Sekolah Menengah Kejuruan (Studi Kasus pada SMK Negeri 2 Bukittinggi) - Nanda Shalihin; Denny Sagita Rusdianto; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PKL (Field Work Practice) is an activity to provide work experience to students. In its implementation there are three stages, namely registration, placement, and reporting. At the registration stage, the time spent is relatively long. This is due to the large number of students. At the placement stage, the head of the department must collect student data and place students according to the city allowed by each student's parents, this also takes quite a long time. In addition, at the reporting stage, the reporting document has a risk if at any time the document is lost or damaged. Therefore, this research offers a solution to these problems. The development of the Vocational High School Field Work Practice Management System is based on a case study at SMK Negeri 2 Bukittinggi. System development begins with the requirements engineering stage to testing and implementing an object-oriented approach. In this development there is one non-functional requirement and 46 functional requirements in requirements engineering. Implementation of the system using the help of the Laravel framework. The unit test got an average V(G) result of 2 paths, and the validation test got 100% valid results, and the system Compatibility test managed to run the system smoothly on Firefox, Opera, safari, chrome, iOS, android, IE, and browsers. Edge. In the next research, it is recommended to implement it in the form of a Mobile App and improve system security.